Feeding and nutrition of tropical farmed fish and shrimp: pellet water stability, in vitro protein digestion, comparison of inert markers, evaluation of practical feeds, and dietary amino acid requirement - Raggi, Thiago (2016)
The aim of this thesis was to evaluate the feeding and nutrition of tropical farmed fish and shrimp, targeting its applicability to aquaculture farming. The study of the actual panorama of aquafeed quality for tilapia Oreochromis niloticus and shrimp Litopenaeus vannamei farmed in Brazil showed that the proximate compositions between the analyzed feeds were mostly consistent with the declared values from the manufacturers, however, the feed water stability showed the opposite; the in vitro pH-stat species-specific method to determine the protein degree of hydrolysis (DH) showed to be a useful tool to evaluate feed quality; and NIRS technique can be used in many applications throughout the aquafeed industry, being an efficient tool for rapidly assessing feed quality in terms of DH. A second study evaluated the acid-insoluble ash (AIA) and chromic oxide (Cr2O3) as inert markers and feed processing method (industrial extruded vs. laboratory cold pelleted) to determine apparent digestibility coefficient (ADC) of dry matter and crude protein of juvenile L. vannamei. The AIA showed to be an effective natural endogenous marker for digestibility trials with L. vanammei, however, for commercial feeds attention should be paid to feed AIA level; the extruded feed showed better animal performance than the cold pelleted feed, however, ADC of both feeds were not significantly different from each other. Further, two feeding trials were conducted with juvenile cobia Rachycentron canadum: (1) feeding trial conducted within floating net cages to test the nutritional efficacy of different dietary feeding regimes ranging from the use of trashfish, in-house formulated feeds, to dry commercial extruded marine fish feed; and (2) feeding trial conducted within indoor water-recirculated tanks to test the nutritional efficiency of different potential dietary fishmeal replacers within dry in-house prepared diets. Generally, fish performance was superior in the net-cage feeding trial compared with the indoor water-recirculated tank trial; overall, the fish growth and performance of the experimental diets were very similar, showing that the alternative ingredients could be included and replace part (50%) of the fishmeal component; the results from both trials concluded that the cobia requires practices diets with high levels of crude protein and lipid, and the inclusion of alternative plant-based and terrestrial animal protein sources was possible; the quantitative essential amino acid (EAA) requirement values estimated by the protein accretion method was highly correlated to the average of each of the EAA requirement for the species of carnivorous fish reported in the literature, and could be recommended for formulation of commercial feed for cobia R. canadum. Finally, a tentative to quantify the total sulfur amino acid requirement of juvenile Florida Pompano Trachinotus carolinus, was performed using combinations of various soybean protein products in order to develop cost-effective and environmentally-friendly diets. Although there was an apparent tendency in the results, the range of methionine levels employed in this study may not have been broad enough to accurately measure the dietary concentration necessary to estimate the total sulfur amino acid requirement; in addition, high variation results among the three replicates per diet did not provide sufficiency robustness for its estimation; this study within 45 days should not have been enough to show significant differences among the treatments. Long term feeding trials would be recommended from fingerling/juvenile to market size with full nutritional and economic evaluation of results.